The Effects of Taxpayer’s Motivation, Commitment and Tax Sanctions on the Level of Individual Taxpayer’s Obedience at Small & Medium-Sized Entreprises (SMEs) in Jakarta - Hendra, Tjie; Alusinsing, Daniel; Murtanto, Murtanto; Faisal, Aris Riantori (Budapest International Research and Critics University, 2022)
The study is aimed to analysis the effects of taxpayer’s motivation, commitment and tax sanctions on the level of individual taxpayer’s obedience at Small & Medium-Sized Entreprises (SMEs) in Jakarta. The study used the quantitative descriptive method, a research design aimed to analyze the correlations or effects among variables by using statistic approaches and mathematic equations. The research involves the individual taxpayers whose have proffessions as Small & Medium-Sized Entreprises (SMEs) to be samples. The data collecting technique is carried out by distributing questionnaire to 200 respondents using the convenience sampling technique, in which only respondents are willing to fill out the questionnaire to be used as study samples. The hypotheses testing technique is carried out by using multiple regression method to test research hypotheses. The results indicated that either partially or simultaneously there are positive effects of taxpayer’s motivation, commitment and tax sanctions on the level of individual taxpayer’s obedience at Small & Medium-Sized Entreprises (SMEs) in Jakarta. These influences are based on the strengthening of the interrelationships among the independent variables which then increase the level of individual taxpayer’s obedience. In this case, the existence of tax sanctions increases the taxpayer’s motivation and commitment so that their level of taxpayer’s obedience increases.